Perceptual orientation of housing floor finishes choice and preference - Zinas, Z. (Academic World Education & Research Center, 2014)
Housing intetiors are the environments where most of life's activities take place. The finishing of this housing interior is of paramount significance, and house owners and prospective house owners always give premium to how their housing interiors are finished. The choices of finishes materials always provoke and create certain motivations and perceptual orientations while these choice and preference activities are being undertaken. This paper presents the perceptual orientation with respect to housing floor finish choices and preferences in Yola, Nigeria. The study was framed within the Means-End Chain (MEC) model, and preferences. 15 respondents were interviewed using the laddering interviewing technique. Prior to the laddering interviews, a structured questionnaire survey was administered to 150 respondents to elicit the relevant housing floor finishes attributes. The results revealed that eleven (11) identified unique perceptual orientation pathways were established, motivated by five user values; intervened by four expected functional affordances. The findings reinforced the design expectations of housing users/owners for finishing their housing interiors.